DESIGN AND CONSTRUCTION OF ROTATING ULTRA-SONIC RANGING DEVICE FOR ENVIRONMENTAL SENSING - DIPTA NANDAVIRI (NIM : 13206180) ; pembimbing : Dr. Kusprasapta Mutijarsa ; Widyawardana A ,S., ARDYA
In this final project environmental sensing system is constructed and built using rotating ultra-sonic ranging device. This final project is a part of the topography of the environment imaging research that can be applied in various ways, such as measuring the object space, the detector on moving object and mapmaker robot. This system is capable of sensing the topography of the environment within a radius of 360o with four ultrasonic sensors that are mounted perpendicularly to each other and work simultaneously. Servo motor is used to rotate all four sensors 90o back and forth, thus obtained imaging of topography of the environment within radius of 360o. As a main controller of the motor servo and the sensors, Arduino Mega microcontroller module based on Atmega 1280 is used. The data of the sensors and the servo position are transferred to the computer using a USB serial communications in Arduino Mega module. The results of this scan will be mapped into the radar screen on a computer using a software called Processing. The experiment result concluded that the system can create maps of the environment within a radius of 360o. Speed of the system to produce the map depends on the size of the environment. The sensor detection capability is measured 3 cm to 377 cm from the mouths of the sensor. The imaging result shows error that there exist an extended room at each corner of the room.